The Directing in the Perspective of Islamic Educational Management - Mukhlisin, Mukhlisin; Made Saihu (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
In Islamic management, the concept of directing (taujih) plays a crucial role in guiding the direction and alignment of organizational activities to ensure they operate effectively and efficiently. This article discusses the concept of taujih from an Islamic perspective, grounded in the principles of the Qur’an and Hadith, along with examples of its implementation in the leadership of Prophet Muhammad SAW and the Khulafa' al-Rashidin. Taujih is understood as the role of a leader in providing guidance, direction, and moral encouragement to organizational members in order to achieve the established goals. Tansiq, on the other hand, is defined as the process of adjusting and harmonizing the tasks, functions, and responsibilities of individuals and work units to create organizational synergy. Islamic values such as justice, wisdom (hikmah), brotherhood (ukhuwah), openness, and consultation (shura) form the foundational principles in applying this concept. This article also identifies various challenges that often arise in the implementation of taujih and tansiq, such as internal conflicts, weak communication, and unclear role structures. As a solution, Islam emphasizes the principles of consultation (shura), proportional task distribution, and strengthening solidarity and collaboration. The implementation of taujih and tansiq in accordance with Islamic values is expected to enhance organizational effectiveness, strengthen work solidarity, and present an ethical and spiritually-oriented leadership model.